Social Networking Sites and Their Implications For The Moral Values of Preschool children: : Analysis of You Tube Content Provided to children - BENMILOUD, Chems el Houda; LAALAOUI, Khaled (Journal of Human Sciences, 2020)
Thestudy aimed atfinding out the impact of social networking sites You Tube as a model on thechild's moral values, based on the extent of the site's popularity and its useby children. Despite the many problems raised about this site, the study of itsimpact on this important segment of society is still very weak, So we triedhard to highlight the impact of these sites on the values ​​of the preschoolchild by using the content analysis, which enables us to highlight the values​​contained in a sample of these programs and compare them with the originalethical values.